Efficient Preparation of Chitooligosaccharide With a Potential Chitosanase Csn-SH and Its Application for Fungi Disease Protection - Cui, Dandan; Yang, Jin; Lu, Bosi; Shen, Hong (Frontiers in Microbiology, 2021)
Chitosanase plays a vital role in bioactive chitooligosaccharide preparation. Here, we characterized and prepared a potential GH46 family chitosanase from Bacillus atrophaeus BSS. The purified recombinant enzyme Csn-SH showed a molecular weight of 27.0 kDa. Csn-SH displayed maximal activity towards chitosan at pH 5.0 and 45 ℃. Thin-layer chromatography (TLC) and electrospray ionization-mass (ESI-MS) indicated that Csn-SH mainly hydrolyzed chitosan into (GlcN)2, (GlcN)3 and (GlcN)4 with an endo-type cleavage pattern. Molecular docking analysis demonstrated that Csn-SH cleaved the glycoside bonds between subsites -2 and +1 of (GlcN)6. Importantly, the chitosan hydrolysis rate of Csn-SH reached 80.57% within 40 min, which could reduce time and water consumption. The hydrolysates prepared with Csn-SH exhibited a good antifungal activity against Magnaporthe oryzae and Colletotrichum higginsianum. The above results suggested that Csn-SH could be used to produce active chitooligosaccharides efficiently that are biocontrol agents applicable for safe and sustainable agricultural production.